Instrumental Colour Profile of Dieteic Sandesh as Function of Ingredients Using Response Surface Methodology - Khamrui, Kaushik (Indian Journal of Dairy Science, 2014)
For growing the sale of product consumer preferences are taken as priorities which can approximately be judged by the quality of food. Colour is first parameter to assess the quality of food product and hence is the purpose of present study. Effect of varying fat content, WPC-70, sucralose and sorbitol addition was investigated on the colour values i.e. L*, a*, b* of dietetic sandesh (chhana-based Bengali sweet) using response surface methodology. All variables were found to affect the colour values significantly. Fat removal increases the whiteness of sample (L* value) but WPC-70 addition increases the melanoidin content (redness) (a* value). Sucralose was found to affect only yellowness of product (b* value). Sorbitol addition increases the darkness in sample and reduces yellowness. Optimized solution with maximum desirability of 0.980 was found to be milk fat-1%, WPC-70-0.5%, sorbitol-15% and sucralose-600ppm.